The regularity of political science in south Korean and Taiwan academic contexts - Beidollahkhani, Arash (Teorija in praksa, 2023)
The democratisation and economic growth of the Asian Tigers, specifically South Korea and Taiwan, brought structural changes to the academic systems of these countries, particularly in the fields of political science and international relations. The article aims to provide a comprehensive and hybrid view on the regularity of political science in the academic environments (university systems) of East Asian countries with a focus on South Korea and Taiwan through the observational analysis method and a historical-sociological mechanism. The findings are summarised, where it is argued that the pentagonal democratic citizenship system (legal, political, cultural, social, economic) as well as the establishing of structural and updated political-economic relations with the main powers in the international system are the two crtitcial factors that have contributed to the adjustment of political science in East Asian countries, including South Korea and Taiwan. The article concludes that, along with the international and domestic developments in South Korea and Taiwan, political science underwent structural changes and is becoming more regulated and structured.
Keywords: Demokracija; Družbene institucije; institution; political science, democracy, institution; Politične vede